2015
DOI: 10.4028/www.scientific.net/kem.638.130
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Centromedullary Nailing with Implant Failure

Abstract: Centromedullary nailing is the most preferred surgical technique for the treatment of lower limb fractures and sometimes also on the upper extremity. It is a minimal invasive surgical intervention used mainly for long bones fractures that permits treatment without opening the fracture site thus preserving the local vascularization. With the improved knowledge and understanding of the fracture pattern and of the implantation technique good stability and rapid bone healing is obtained.We present a study on 8 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…We have to take into account that the size of metallic debris is under 50 nm comparing to PE debris size regularly under 0,1 μm [11]. It has been proven that size and shape of metallic debris change with severity of wear [12][13][14][15]. The small size of the metallic debris increases tremendously the host-particles interface and consequently enhances host inflammatory response.…”
Section: Metallic Debris Is the Trigger Points And They May Results B...mentioning
confidence: 99%
“…We have to take into account that the size of metallic debris is under 50 nm comparing to PE debris size regularly under 0,1 μm [11]. It has been proven that size and shape of metallic debris change with severity of wear [12][13][14][15]. The small size of the metallic debris increases tremendously the host-particles interface and consequently enhances host inflammatory response.…”
Section: Metallic Debris Is the Trigger Points And They May Results B...mentioning
confidence: 99%
“…An important issue are the design of the orthopedic implants because are used different processing techniques of the metallic biomaterials in order to obtain various types of orthopedic implants like screws, plates, wires, pins, that could affect the metallic materials microstructure, mechanical properties and implant surface [16,18,19]. The processing techniques of metallic biomaterials and the excesive biomechanical loading are the main causes for metallic implant failure, as is mentioned in various studies [20][21][22][23]. Even various studies describe now the potential of biodegradable metals and metallic glass for orthopedic implants, we consider that the classical metallic biomaterials like titatinium and his alloys are still the best option available for trauma implants [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Various papers evaluate the failure causes of different orthopaedic implants but it was observed that most of them didn't follow a specific protocol for implant or material analysis because they use different microscopically techniques for these analyses [25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
mentioning
confidence: 99%